Preventing delayed cracks in SUS304 deep drawn cups using extreme blank holding forces aided by nanolubrication / Muhammad Shafiq Ibrahim - Muhammad Shafiq, Ibrahim (2020)
This study was to investigate the formation and reformation of delayed cracks of SUS304 cylindrical drawn cups under elevated blank holding force (BHF) from 8~32 kN with 1~3 wt% SiO2 nanolubricants concentrations. The widest crack-free BHF range i.e. from 29 ~ 31 kN was determined for 2 wt% of SiO2 in the experiment. Delayed cracks were also observed below and beyond this BHF range. There was an increment of frictional force at the cup flange region when entering the crack-free BHF range, as proven by the rebound in sidewall thickness, relative intensity of α′-martensite, elongated height and drawing force beyond 28 kN. The crack reformation after exiting crack-free BHF range was due to the worsened nanolubricant tribological performance when undergoing excessive pressure, hence, allowing high friction induction. The α’–martensite had the highest relative intensity (%) at 93.7 % for BHF = 28 kN, leading to the delayed cracks. The relative intensity slightly decreased after the peak within the crack-free range with intensities ranging from 83.8 ~ 89.9 % before experiencing a sharp decrease to 50.7 % for 32 kN leading to the reformation of the cracks again. Residual stresses were developed along the outer surface of the cup due to the unbending of the material when the material left the draw die profile, hence, the increase in frictional force in the radial direction along the flange surfaces reduced the circumferential tensile residual stress of the cup, particularly at 80 % cup height. The elimination of the cracks was attributed to the decrease in intensity of the α’-martensite and the lower tensile stress gradient. The minimum BHF required for eliminating the cracks was hardly altered by the increase in concentration of SiO2.